2001
DOI: 10.14430/arctic798
|View full text |Cite
|
Sign up to set email alerts
|

Summer Movements of Radio-tagged Arctic Charr (<i>Salvelinus alpinus</i>) in Lake Hazen, Nunavut, Canada

Abstract: ABSTRACT. Radiotelemetry was used to determine whether Lake Hazen arctic charr (Salvelinus alpinus) were anadromous and to determine movements of the charr within the lake. In 1995 and 1996, 62 and 55 charr, respectively, were captured, radio-tagged, and released back into the lake. A fixed data acquisition system recorded limited movements of radio-tagged charr in the upper reaches of the Ruggles River, the only outlet from the lake to the sea, in 1995. When movements of radio-tagged charr within Lake Hazen w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…1, Table 1). With the exception of Ruggles River (Lake Hazen, Ellesmere Island), all outflows of the study lakes do not allow for migration, and Lake Hazen char are confirmed to be lake resident [35]. Selection of sites was constrained by accessibility and guided by past sampling campaigns, and/or current monitoring programs.…”
Section: Site Selectionmentioning
confidence: 99%
“…1, Table 1). With the exception of Ruggles River (Lake Hazen, Ellesmere Island), all outflows of the study lakes do not allow for migration, and Lake Hazen char are confirmed to be lake resident [35]. Selection of sites was constrained by accessibility and guided by past sampling campaigns, and/or current monitoring programs.…”
Section: Site Selectionmentioning
confidence: 99%
“…Detailed morphological and meristic studies by Reist et al (1995) demonstrated the forms differed substantially in body form, colour, number of pyloric caecae, caudal peduncle length, and pelvic and pectoral fin lengths, but could not establish whether differences arose for trophic or migratory reasons. More recently, analyses of the distribution of strontium in otoliths (Babaluk et al, 1997) and radio-tagging (Babaluk et al, 2001) demonstrated that both forms are non-anadromous. Results suggest that differences in growth trajectories during the adult phase arise from differences in feeding strategies and habitat use.…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of river icing, sediment typically aggrades upstream of the icing and leads to braided channels [Harden et al, 1973;Bennett et al, 1998] (e.g., Figure 2a). These sediment deposits and channel morphologies provide a multitude of unique and important ecosystem benefits, including organismal habitat and refugia for key species such as Chinook salmon [Babaluk et al, 2001;Bradford et al, 2001]. Alterations of river flows and deposits associated with icings affect economically important civil infrastructure and recreation opportunities through, for example, roadway and rafting hazards [Morse and Wolfe, 2015].…”
Section: Discussionmentioning
confidence: 99%